المساعدة والرقابة القضائية للعملية التحكيمية في النظام السعودي دراسة تحليلية: Judicial Assistance and Supervision of the Arbitration Process in the Saudi Judiciary System: An Analytical Study - Al Anaz, Jumaah Awwad; Buang, Ahmad Hidayat; Daud, Mohd Zaidi (Jurnal Fiqh, 2020)
This research includes studying some aspects of oversight and judicial assistance for the arbitration process in the light of the Saudi arbitration articles issued in 1433 AH, and based on an analytical study covering 30 provisions directed to the Court of Appeal, whether it is due to nullity or judicial assistance in order to find out the extent of the Saudi judiciary interference in the arbitration process, and whether this intervention - auxiliary or supervisory - is an obstacle to the implementation of the arbitration provisions. This research is divided into two topics: first, the intervention of the state auxiliary judiciary for the arbitration process, and second , the intervention of the state supervisory judiciary in the arbitration process. These two topics include an analytical study to measure the extent of state judiciary interference in the arbitration process, whether it is auxiliary or supervisory. A descriptive analytical approach is used to find a solution and to approach the research problem. The study reaches some conclusions: since judge assistant roles for arbitration are exceptional roles, arbitration cannot be separated from the judiciary for the reason that the arbitration panel is far from having the power to compel and issue the penalty. In addition, states shall implement the arbitration decision, in order that the content of the judgment does not conflict with public order and internal sovereignty. It should be stressed that the formal judiciary should realize the purpose for this oversight that arbitration provisions are free from fundamental defects and implementing them would disrupt this effectiveness thus undermining the credibility of arbitration as an alternative mechanism on the judiciary to resolve disputes.